2011
DOI: 10.1111/j.1469-185x.2011.00213.x
|View full text |Cite
|
Sign up to set email alerts
|

Pollinator‐prey conflict in carnivorous plants

Abstract: Most carnivorous plants utilize insects in two ways: the flowers attract insects as pollen vectors for sexual reproduction, and the leaves trap insects for nutrients. Feeding on insects has been explained as an adaptation to nutrient-poor soil, and carnivorous plants have been shown to benefit from insect capture through increased growth, earlier flowering and increased seed production. Most carnivorous plant species seem to benefit from insect pollination, although many species autonomously self-pollinate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 96 publications
1
35
0
Order By: Relevance
“…These results are analogous to the few comprehensive reproductive ecology studies conducted in Europe for other Pinguicula species (Molau ; Jürgens et al . ; e.g. P. longifolia [García et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are analogous to the few comprehensive reproductive ecology studies conducted in Europe for other Pinguicula species (Molau ; Jürgens et al . ; e.g. P. longifolia [García et al .…”
Section: Discussionmentioning
confidence: 99%
“…; Heslop‐Harrison ; Jürgens et al . ). These studies have shown that Pinguicula species are self‐compatible and can be autogamous or xenogamous, are mostly pollinated by Diptera and Hymenoptera, and have relatively high fruit and seed sets.…”
Section: Introductionmentioning
confidence: 97%
“…A pollinator–prey conflict (PPC) may be described as a trade‐off between increasing the risk of pollinators being trapped to gain more resources (that can in turn be invested in reproduction) vs. reducing the effectiveness of traps to increase reproductive success via pollen import and export through pollinators (Jürgens et al . ). It seems possible that the pollinator–prey conflict can be partly resolved through the evolution of features that reduce the risk of pollinators being trapped, for example by increasing the distance between prey capturing leaves and flowers (Anderson & Midgley ; Anderson ).…”
Section: Introductionmentioning
confidence: 97%
“…Another way to reduce the risk of pollinators being trapped might be to use specific olfactory and/or visual cues to lure non‐pollinating animals to traps, while at the same time attracting pollinators to flowers (see Jürgens et al . ). However, our knowledge of the importance of visual and olfactory cues in carnivorous plants for attracting prey insects is still very limited.…”
Section: Introductionmentioning
confidence: 97%
“…The presence of insect inquilines, which are able to leave the pitcher after metamorphosis, seems to be unresolved in the European populations. A final possible source of Dipteran DNA could be from the pollinators of S. purpurea (Jürgens, Sciligo, Witt, El‐Sayed, & Suckling, ), as it is possible that our metabarcoding approach detects Dipteran DNA which has been transferred during these visits. Although the particular inquiline and prey species differ between native and allochthonous populations, invertebrate functional groups may be important biological predictors of pitcher plant range, as inquiline successional stages are thought to be similar in pattern (Gray, Akob, Green, & Kostka, ; Zander et al., ).…”
Section: Discussionmentioning
confidence: 99%